Characterization on the recycling of waste seashells with Portland cement towards sustainable cementitious materials. (20th May 2019) - Wang, Junjie; Liu, Engui; Li, Liang
Abstract: This work introduces a cleaner production practice of transforming waste seashells into new minerals for sustainable cementitious materials. Waste seashells were recycled into fine powder through regular crushing and ball-milling processes. Multi-scale studies characterized systematically the reaction mechanisms of waste seashell powder in ordinary Portland cement system. Seashell powder was studied as both a cement replacement and an additional mineral filler, and its roles were explored through workability of fresh cement mixtures, hydration of cement, and mechanical behaviors of hardened cement mixtures. The results indicated that seashell powder enhanced the hydration of cement through its physical and chemical interactions with both cement clinker phases and hydration products. The mechanical strength of hardened cement mixtures was directly improved when the seashell powder was used as an additional filler. Additions of seashell powder, either as a cement replacement or an additional filler, modified the rheological behaviors of fresh cement mixtures. The hydrated CSH matrix phases developed with seashell powder were clearly enriched by the embedded well-dispersed nanosized clusters (with diameter around 5–10 nm). Parallel comparisons between seashell powder and limestone powder confirmed the higher surface properties and chemical reactivities of seashell powder than limestone powder in cement system. Graphical abstract: Image 1 Highlights: Recycling waste seashells to be renewable biomaterials. Grounded waste seashells used as a new supplementary cementitious material. Seashell powder enhances the hydration of cement. Seashell powder modifies the rheology of cement paste. Seashell powder is more reactive in cement than limestone powder.